Presumptive Development of Fibrotic Lung Disease From Bordetella bronchiseptica and Post-infectious Bronchiolitis Obliterans in a Dog - Jaffey, Jared A.; Harmon, Mark; Masseau, Isabelle; Williams, Kurt J.; Reinero, Carol (Frontiers in Veterinary Science, 2019)
A 7-month-old Miniature Poodle acquired from a pet store developed cough and subsequently respiratory distress compatible with Bordetella bronchiseptica infection. Partial but incomplete resolution of clinical signs and thoracic radiographic/computed tomographic imaging lesions were noted including with use of susceptibility-guided antimicrobials. Additionally, a concern for an infectious nidus led to left cranial lung lobectomy at 9 months of age. Histopathology predominantly revealed polypoid and constrictive bronchiolitis obliterans (i.e., small airway disease). Intermittent antimicrobial administration over the next 5 years failed to blunt progressive clinical signs. At 8 years, necropsy confirmed severe airway-centered interstitial fibrosis. This pattern of fibrosis was strongly suggestive of underlying small airway disease as the trigger. In retrospect, post-infectious bronchiolitis obliterans (PIBO), a syndrome in young children caused by pulmonary infections but not yet recognized in pet dogs, likely initiated a pathway of fibrosis in this dog. In dogs with risk factors for community-acquired pathogens such as Bordetella bronchiseptica, PIBO is a differential diagnosis with development of severe, persistent respiratory signs incompletely responsive to appropriate antimicrobials. Untreated PIBO may lead to airway-centered interstitial fibrosis. Future study is required to determine if targeted therapy of PIBO could alter the course of end-stage pulmonary fibrosis.